2011
DOI: 10.2147/ijn.s22337
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and in vitro release evaluation of newly synthesized palm kernel oil esters-based nanoemulsion delivery system for 30% ethanolic dried extract derived from local Phyllanthus urinaria for skin antiaging

Abstract: Background Recently there has been a remarkable surge of interest about natural products and their applications in the cosmetic industry. Topical delivery of antioxidants from natural sources is one of the approaches used to reverse signs of skin aging. The aim of this research was to develop a nanoemulsion cream for topical delivery of 30% ethanolic extract derived from local Phyllanthus urinaria ( P. urinaria ) for skin antiaging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 40 publications
0
34
1
Order By: Relevance
“…Their findings indicate that lower globule size results in higher release [30]. On the contrary, in our study, formulation C10 with the largest globule size showed maximum drug release.…”
Section: Physical Evaluation Of Emulgelscontrasting
confidence: 82%
“…Their findings indicate that lower globule size results in higher release [30]. On the contrary, in our study, formulation C10 with the largest globule size showed maximum drug release.…”
Section: Physical Evaluation Of Emulgelscontrasting
confidence: 82%
“…It is well recognized that not every composition allows achievement of nanoemulsions (Shakeel et al, 2010;Mahdi et al, 2011). Thus, nanoemulsion region obtained in the present study may be important for further studies with copaiba oleoresin, since these types of formulations could be obtained with compositions within this zone.…”
Section: Resultsmentioning
confidence: 71%
“…2), constituted by 25 formulations. The high percentage of nanoemulsions obtained (approximately 80%) may be attributed to heating and mechanical energy achieved by the T25 Ultra-Turrax, which have been associated to an extended oil-in-water miniemulsion region (Mahdi et al, 2011). It was also observed that some formulations within nanoemulsion region were transparent and reached mean droplet size below 100 nm.…”
Section: Resultsmentioning
confidence: 91%
“…; Mahdi et al . ). However, it is not effective as an emulsifier when used solely because its small neutral head group does not generate strong steric or electrostatic repulsion.…”
Section: Discussionmentioning
confidence: 97%